Making the case for community involvement in research on climate and health: opportunities and lessons - Black, Gillian F.; Jamrozik, Euzebiusz; Khan, Wesaal; Peralta, Stephanie; Havenga, Benjamin; Merritt, Maria W.; Kelley, Maureen (Frontiers in Climate, 2024)
Advancing climate change is an urgent global driver of human disease with some of the world’s most marginalized communities being at highest risk. In response to this compound threat, scientific studies exploring the intersections of climate and health are gaining momentum, yet sparse attention is currently paid to models of research that engage and involve those who are most affected. This is a crucial moment for the global health field to take up valuable lessons from the relatively few climate-health studies that have purposefully brought scientists together with communities and members of the wider public, via established approaches such as community-based participatory research and citizen science, to reduce health risks and better understand the deeper determinants of disease. Through a scoping literature review of PubMed and qualitative framework analysis, we investigate scientific, ethical, and social justice rationales that have motivated scientists to involve communities, including Indigenous groups, and other public stakeholders in climate-driven health research to varying degrees in different global contexts. We also examine the benefits of diverse forms of engagement and show that involving communities in research at the climate-health nexus has, for example, generated co-produced adaptation strategies that respond appropriately and effectively to priority health hazards. In addition, our findings demonstrate limitations, challenges, and ethical considerations that can arise when engaging communities in climate-health research. We argue that ethically engaging and involving communities and the wider public in research at the intersection of climate change and health is imperative for identifying relevant research priorities, promoting responsiveness that can appropriately fill gaps in at-risk settings, and advancing social justice. Our paper offers a range of examples of research designs and activities to guide scientists working in this emerging interdisciplinary field, inform funders seeking to support innovative and potentially transformative research, and contribute to global health policy.